Adaptation amidst Prosperity and Adversity : Insights from Happiness Studies from around the World - Graham, Carol (World Bank, 2013)
Some individuals who are destitute report to be happy, while others who are very wealthy report to be miserable. There are many possible explanations for this paradox; the author focuses on the role of adaptation. Adaptation is the subject of much work in economics, but its definition is a psychological one. Adaptations are defense mechanisms; there are bad ones like paranoia, and healthy ones like humor, anticipation, and sublimation. Set point theory—which is the subject of much debate in psychology—posits that people can adapt to anything, such as bad health, divorce, and extreme poverty, and return to a natural level of cheerfulness. The author's research from around the world suggests that people are remarkably adaptable. Respondents in Afghanistan are as happy as Latin Americans and 20 percent more likely to smile in a day than Cubans. The findings suggest that while this may be a good thing from an individual psychological perspective, it may also shed insights into different development outcomes, including collective tolerance for bad equilibrium. The author provides examples from the economics, democracy, crime, corruption, and health arenas.